Peningkatan Metode Pembelajaran Bahasa Arab Yang Sesuai Pada Siswa Madrasah Diniyah Awaliyah - Rokayah, Yayah; Annisa, Akke Azhar; Prasetiadi, Yan Septian (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Increasingly advanced technology has made it easier to access various aspects, including the culture of various countries, which makes it possible to exchange information and adopt technology and knowledge from these countries. Language plays an important role in supporting this. Language skills can be instilled from an early age, especially in children aged between 6-10 years, which is an important period for their intellectual and personality development. At this age, children's brains have the ability to absorb information quickly, especially things that are interesting to them, including in the context of language learning. This research aims to explore the effectiveness of Arabic language learning methods in the learning process of students at the Diniyah Awaliyah Madrasah. This research uses qualitative research, with data collection through interviews, observation and documentation. The research results showed that the three learning methods used (hifdzil method, game method, and singing method) were proven to be effective in increasing children's knowledge. This is reflected in students' ability to memorize vocabulary, their ability to pronounce Arabic letters fluently, increased memory, and their ability to be creative. This method can also motivate students to learn more.